흐름장에서 인공용승구조물의 블록투하 및 용승효과에 관한 실험적 연구 - 전용호(YONG-HO JEON); 이경선(GYUNG-SUN LEE); 강윤구(YOON-KOO KANG); 류청로(CHEONG-RO RYO) (Han-guk haeyang gonghak hoeji (Online), 2007)
The multiplication equipment of marine products with artificial upwelling structures could be useful in the fishing grounds near coastal areas. Artificial upwelling structures could move the inorganic nutrients from the bottom to the surface. Artificial upwelling structures have been used to improve the productivity of fishing grounds. Until now, research on artificial upwelling structures has been related to the distribution of the upwelling region, upwelling structures, and the marine environment. However, little work on the optimum design of the rubber-mound artificial upwelling structures has been done to increase the efficiency of drawing up the inorganic nutrients. This study investigated the optimum cross-section of rubber-mound artificial upwelling structures by means of hydraulic experiments. The hydraulic experiments include the falling test of rubber. Based on the results of the falling test, the relationship between the length of the rubber mound and water velocity, and the relationship between the shape of the rubber and the stratification parameter were established. In addition, the effect of the void ratio of various artificial structures on the stratification parameter was studied. From the experiment, it was found that upwelling could be enhanced when the ratio of structure height to water depth was 0.3 and stratification parameter was 3.0. The upwelling was not improved when the void ratio exceeded 0.43. The optimum size of rubber mounds was determined when the incident velocity was influenced by the mean horizontal length rather than size of block.